Small Extracellular Vesicles Released from Bioglass/Hydrogel Scaffold Promote Vascularized Bone Regeneration by Transferring miR-23a-3p - Hu H; Zhang H; Bu Z; Liu Z; Lv F; Pan M; Huang X; Cheng L (International Journal of Nanomedicine, 2022)
Hongxing Hu,1 Hang Zhang,2 Ziheng Bu,3 Zhongtang Liu,3 Fang Lv,4,5 Mingmang Pan,5 Xuan Huang,3 Liming Cheng1 1Department of Orthopedics Tongji Hospital Affiliated to Tongji University, Tongji University School of Medicine, Shanghai, People’s Republic of China; 2School of Mechanical Engineering, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 3Department of Orthopedics Changhai Hospital Affiliated to the Second Military Medical University, Shanghai, People’s Republic of China; 4Shanghai Key Laboratory of Regulatory Biology, Institute of Biomedical Science and School of Life Science, East China Normal University, Shanghai, People’s Republic of China; 5Department of orthopedics, Shanghai Fengxian District Central Hospital, Shanghai, People’s Republic of ChinaCorrespondence: Xuan Huang, Department of Orthopedics Changhai Hospital Affiliated to the Second Military Medical University, 168 Changhai Road, Shanghai, People’s Republic of China, Tel +86 18930172772, Email 11791709@qq.com Liming Cheng, Department of Orthopedics Tongji Hospital Affiliated to Tongji University, Tongji University School of Medicine, 389 Xincun Road, Shanghai, People’s Republic of China, Tel +86-21-56051080, Email limingcheng@tongji.edu.cnBackground: The treatment of critical-size bone defect is a great difficulty in orthopedics. Osteogenesis and angiogenesis are critical issue during the process of bone repair and remodeling. Mesenchymal stem cells (MSCs)-derived exosomes have the same therapeutic effect to MSCs-based therapies. The effect of human umbilical cord MSCs-derived sEVs (hUC-MSCs-sEVs) on vascularized bone regeneration and the potential mechanism remains to be investigated. Herein, we aimed to explore the therapeutic effect and the mechanism of hUC-MSCs-sEVs on critical-size bone defect.Methods: To investigate the potential osteogenesis and angiogenesis effects of sEVs in vitro, we extracted sEVs from hUC-MSCs, and then sEVs were co-incubated with BMSCs and HUVECs. We next investigated the effect and potential mechanism of sEVs on the effects of osteogenesis and angiogenesis. We fabricated 3D-printed bioglass scaffold with Gelma/nanoclay hydrogel coatings to load sEVs (BG-gel-sEVs) to ensure in vivo sustained efficacy of sEVs. Finally, the skull defect model was used to evaluate the capacity of vascularized bone regeneration of the composited scaffolds.Results: hUC-MSCs-sEVs facilitated calcium deposition and the endothelial network formation, inducing osteogenic differentiation and angiogenesis by delivering miR-23a-3p to activate PTEN/AKT signaling pathway. Additionally, the BG-gel-sEVs composited scaffold achieved vascularized bone regeneration in vivo.Conclusion: This finding illuminated that hUC-MSCs-sEVs promoted osteogenesis and angiogenesis by delivering miR-23a-3p to activate PTEN/AKT signaling pathway, achieving vascularized bone regeneration.Keywords: small extracellular vesicles, bone regeneration, angiogenesis, miR-23a-3p, bioglass scaffolds